Human Rights Education for Law Enforcement Personnel - Biel Portero, Israel; Vega Rosario , Camilo Andrés (Scientific journal of social studies, 2025)
Human rights education comprises a broad set of activities that contribute to the realization of human rights, not only favoring their protection and promotion, but also preventing potential violations thereof. Today, human rights education is constituted as an autonomous field that seeks the construction of a universal culture of human rights. Human rights education is especially important for the public forces, because as agents of the State, they are responsible for respecting and protecting the human rights of all citizens. However, the initiatives to implement this component are far from being sufficient.